2005
DOI: 10.1109/lpt.2005.853530
|View full text |Cite
|
Sign up to set email alerts
|

Improved temperature performance of 1.31-/spl mu/m quantum dot lasers by optimized ridge waveguide design

Abstract: Article:Ray, S.K., Groom, K.M., Hogg, R.A. et al. (5 more ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Figure 6 plots the peak wavelength of the lasing spectrum at 1.1J th for both devices as a function of the device length. 19 For these 5 m wide ridges, a greater internal loss is expected, and as a result the switching takes place at longer cavity lengths. This phenomenon indicates the switching of the laser emission from the ground state to the excited state.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 6 plots the peak wavelength of the lasing spectrum at 1.1J th for both devices as a function of the device length. 19 For these 5 m wide ridges, a greater internal loss is expected, and as a result the switching takes place at longer cavity lengths. This phenomenon indicates the switching of the laser emission from the ground state to the excited state.…”
Section: Resultsmentioning
confidence: 97%
“…Researchers have proposed several methods to further improve the performance of QD lasers, such as modulation doping in QD layers [3]- [6], tunneling injection structures [7], dots-in-a-well (DWELL) structures [8], etc. Within the various investigations on QD lasers, there has been only little effort put into studying the geometrical effects on laser performance [9]. It has been shown that the ridge height, which is controlled by the etch depth during fabrication, is an important parameter for lateral spreading current to achieve low threshold current in quantum well (QW) ridge waveguide lasers [10]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the laser with of m needs larger injection current to lase. However, if the laser ridge is too high m , the sidewall area of the ridge will be large, which will lead to high carrier loss due to interface recombination [9], [12]. Therefore, the laser with of m exhibits larger than the laser with of m. In term of characteristic temperature, the laser with of m has an almost infinite from C to C and operates up to C, while the laser with of m only operates below C and exhibits relatively lower of 325 K from C to C. This could be explained by the temperature dependent behavior of the current spreading characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The slope efficiency and the output power decrease. [7][8][9] In addition, the laser gain profile shifts to higher energy levels. 7,10 These phenomena are due to the movement of carriers to higher energy levels.…”
mentioning
confidence: 99%
“…[7][8][9] In addition, the laser gain profile shifts to higher energy levels. 7,10 These phenomena are due to the movement of carriers to higher energy levels. 10 Previous researches on temperature dependence of L-I curves of QD lasers are under singlewavelength operation.…”
mentioning
confidence: 99%